Integrated system for the management of meloidogyne javanica in potato production - Seshweni, Mosima Dorcus (My University, 2016)
Cultivated potato (Solanum tuberosum L.) cultigens do not have resistant genotypes to root-knot (Meloidogyne species) nematodes. Currently, efforts are underway to introgress nematode resistance in potato breeding programmes, whereas other environment-friendly nematode management strategies are being assessed in various cultigens. Nemafric-BL and Nemarioc-AL phytonematicides have being researched and developed for managing the root-knot nematode whereas Biocult Mycorrhizae are intended to enhance crop productivity through improved absorption of P, which is inherently low in most South African soils. The objectives of the study, therefore, were: (1) to determine the interactive effects of Nemacur (N), Biocult Mycorrhizae (B) and Nemarioc-AL or Nemafric-BL phytonematicide (P) on population densities of M. javanica and growth of potato plants, (2) to investigate the effects of Nemacur (N), Velum (V), Biocult Mycorhizae (B) and Nemarioc-AL or Nemafric-BL phytonematicide (P) on population densities of M. javanica and growth of potato plants. For the microplot experiment, potato cv. ‘Mondial G3’ seeds were sown in 25 cm-diameter plastic pots with 5 000 ml steam-pasteurised river sand and Hygromix-T at 3:1 (v/v) growing mixture in autumn (March-May) 2015. Pots were buried 80% deep into the soil in with 0.5 m inter-row and 0.5 m intra-row spacing. Potato cv. ‘Mondial G3’ seeds were dipped in a mixture of Mancozeb with a wettener for disease management prior to sowing. Appropriate treatments were applied soon after emergence of leaves. Each plant was inoculated by dispensing a mixture of 5 000 eggs and M. javanica J2. Eight treatments, control (N0B0P0), Nemacur (N1B0P0), Biocult (N0B1P0), phytonematicide (N0B0P1), Nemacur × Biocult (N1B1P0), Nemacur × phytonematicide (N1B0P1), Biocult × phytonematicide (N0B1P1) and Nemacur × Biocult × phytonematicide (N1B1P1), were arranged in a randomised complete block xxvi design (RCBD) with 8 replications (n= 64). Under field conditions the study was conducted in summer (October 2015 - January 2016), with 30-cm furrows dug and potato seeds placed in the soil with 30 cm inter-row and 40 cm intra-row spacing. The four treatments, namely, (1) untreated control, (2) Nemacur or Velum (3) Biocult Mycorrhizae and (4) Nemarioc-AL or Nemafric-BL phytonematicide, were arranged in RCBD, replicated three times for the Velum experiment and five times for the Nemacur experiment. At 56 days after inoculation, the second order interaction (N1B1P1) was highly significant (P ≤ 0.01) for eggs in root and total nematodes, contributing 13 and 12% to total treatment variation (TTV) of the two variables, respectively, in the Nemarioc-AL phytonematicide study. Relative to untreated control, the second order interaction (N1B1P1) reduced eggs in root and total nematodes by 42 and 36%, respectively. In both Nemarioc-AL and Nemafric-BL phytonematicide experiments, the combination of phytonematicide and Biocult Mycorrhizae reduced gall rating. Nemacur, Biocult and Nemarioc-AL phytonematicide, the treatment effects were highly significant on eggs, J2 in root and total nematodes, contributing 53, 68 and 57% to TTV of the three variables, respectively. Nemacur, Biocult and Nemafric-BL phytonematicide treatments each was not significant (P ≤ 0.05) for nematodes variables. Both treatments for Nemacur, Biocult and Nemarioc-AL or Nemafric-BL phytonematicides were significant for gall rating, contributing 92 and 70% to TTV of the variable, respectively. In Nemarioc-AL phytonematicide, relative to the untreated control, gall rating was reduced by 48 to 56%, whereas in Nemafric-BL phytonematicide the variable was reduced by 33 to 56%. In the Velum study, Biocult and Nemarioc-AL or Nemafric-BL phytonematicide, the treatment effects in both experiments were highly significant (P ≤ 0.01) on eggs in root, contributing 88% to TTV of the variable. Both treatments from Nemarioc-AL xxvii and Nemafric-BL phytonematicides had no significant effects on all plant variables measured. In microplot, the second order interaction (Nemacur × Biocult × Nemarioc-AL phytonematicide) was highly significant for nematode eggs in root and total nematode. In a three-way matrix, the N1B1P1 interaction had the highest effects on eggs, followed by Biocult alone, then Nemacur alone and then the phytonematicide. The same trend was observed in the three-way matrix for total nematodes. However, in two-way matrix for eggs, Biocult outperformed Nemacur, as was the phytonematicide on J2. In another microplot study, the second order interaction (Nemacur × Biocult × Nemafric-BL phytonematicide) was significant for J2 in soil and roots, with the three-way matrix showing, that Biocult alone had higher effects than the N1B1P1 interaction on J2 in root. A three-way matrix also showed that Nemacur was outperformed by the phytonematicide alone, Biocult alone and the interactions on J2 in soil. In conclusion, Nemarioc-AL and Nemafric-BL phytonematicides could each be used with Biocult Mycorrhizae in the management of population densities of M. javanica in potato production since the impact from Nemacur which is a synthetic nematicide does not have that much difference from that of phytonematicides interacted with Biocult Mycorrhizae.
Thesis (M. Agricultural Management (Animal Production)) -- University of Limpopo, 2016
Keywords: Root-knot (Meloidogyne species) nematodes; Plant-parasitic nematodes; Javanese root-knot nematode; Root-knot nematodes; Potato -- Breeding; Nematode diseases of plants; Plant parasites -- Biological control